The Effect of Democracy and Government Quality on the Level of Income Inequality In BRICS+ Members - Athira Rasyadah Ningtias; Adhi Cahya Fahadayna; Muhammad Abdul Azis (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
Income inequality remains a critical challenge in emerging economies, yet the mechanisms linking democracy and inequality in the BRICS+ bloc remain underexplored. This study investigates how democracy affects income inequality, with a specific focus on governance quality as a mediating factor, in ten BRICS+ countries (Brazil, Russia, India, China, South Africa, Iran, Egypt, United Arab Emirates, Indonesia, and Ethiopia) from 2013 to 2023. Its main contribution is introducing and empirically testing a mediation framework that positions governance as the critical intervening variable in this relationship, a novel approach in the context of this new economic bloc. Using robust panel estimation methods (FGLS, PCSE, and Driscoll-Kraay) to address cross-sectional dependence and heteroskedasticity, the findings reveal a nuanced relationship. While democracy significantly improves governance quality, its effect on inequality is critically mediated by the type of governance dimension strengthened. Crucially, the study provides new empirical evidence that governance quality is a more decisive factor than democracy itself in shaping inequality outcomes within BRICS+. Key policy recommendations include prioritizing investments in primary education, ensuring political stability, and fostering transparent governance to effectively reduce economic disparities in the bloc.